2014
DOI: 10.1021/es404994t
|View full text |Cite
|
Sign up to set email alerts
|

Water Accounting and Vulnerability Evaluation (WAVE): Considering Atmospheric Evaporation Recycling and the Risk of Freshwater Depletion in Water Footprinting

Abstract: Aiming to enhance the analysis of water consumption and resulting consequences along the supply chain of products, the water accounting and vulnerability evaluation (WAVE) model is introduced. On the accounting level, atmospheric evaporation recycling within drainage basins is considered for the first time, which can reduce water consumption volumes by up to 32%. Rather than predicting impacts, WAVE analyzes the vulnerability of basins to freshwater depletion. Based on local blue water scarcity, the water depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 31 publications
0
124
0
1
Order By: Relevance
“…In previous midpoint methods, this varied from two orders of magnitude (0.01-1) for Pfister et al (2009) andBerger et al (2014), and up to 5, 7, and 9 orders of magnitude for Boulay et al (2011b), Hoekstra et al (2012), and Swiss Eco-Scarcity method (Frischknecht et al 2008), respectively, excluding the zero values. This was an important choice which was made with the thresholds placed along the distribution curve in order to keep as much of the natural distribution as possible yet fix the tailing values to the maximum and minimum (see Fig.…”
Section: Spanmentioning
confidence: 98%
See 2 more Smart Citations
“…In previous midpoint methods, this varied from two orders of magnitude (0.01-1) for Pfister et al (2009) andBerger et al (2014), and up to 5, 7, and 9 orders of magnitude for Boulay et al (2011b), Hoekstra et al (2012), and Swiss Eco-Scarcity method (Frischknecht et al 2008), respectively, excluding the zero values. This was an important choice which was made with the thresholds placed along the distribution curve in order to keep as much of the natural distribution as possible yet fix the tailing values to the maximum and minimum (see Fig.…”
Section: Spanmentioning
confidence: 98%
“…While water withdrawal comprises the total water input into a product system, water consumption is defined as the fraction of water withdrawal which has become unavailable for the originating river basin users due to evapo(transpi)ration, product integration, or discharge into other basins and the sea. Hence, subsequently, methods based on water consumption-to-availability (CTA) ratio were developed, with the reasoning that water withdrawn from the environment and released in the same watershed (for cooling purposes for example) does not generally contribute to local water scarcity (Boulay et al 2011c;Hoekstra et al 2012;Berger et al 2014) (even if local impacts may occur between the withdrawal and release points (Loubet et al 2013)). Outcomes from expert discussions within WULCA (Boulay et al 2015a) first identified the need to transition from WTA and CTA towards a demand-to-availability ratio (DTA), in order to better answer the overarching question identified above (Boulay et al 2014) since both ecosystem water demand and human consumption are considered in Bdemand.^The proposal was accepted by a panel of 48 LCA experts from academia, industry, and governmental institutions (Boulay et al 2015a) with, however, one main limitation identified, in addition to the challenge associated with quantifying ecosystem water demand.…”
Section: From Withdrawal-to-availability To Demand-to-availability Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Though this is acknowledged, we do not really understand why non-robust LCIA methods cannot be exchanged by better-existing ones already now (e.g., water and resource depletion)-adding an additional impact category during the ongoing pilot phase was obviously possible. More suitable LCIA methods for water depletion are the methods of Pfister et al [23] and Berger et al [24] and for resource depletion the method of Schneider et al [25,26], which have been available since 2009, thus before the PEF method was published. Furthermore, updating the impact assessment methods only after all 24 PEFCRs are finalized should automatically lead to an invalidity of these PEFCRs as the determined relevant impact categories might not be valid anymore.…”
Section: Impact Assessment Methodsmentioning
confidence: 99%
“…Miano et al [80] considered the influences of climate and human change factors on regional water resources exploitation. Based on local water resource deficiency, Berger et al investigated the possibility of water degradation from perspective of water consumption [81]. Boulay et al believed WSI is the competition pressure among water users, and differentiated water sources and water quality [82].…”
Section: The Influence Of Water Savings and Pollution Discharge Reducmentioning
confidence: 99%